PENGARUH KUALITAS PELAYANAN, HUBUNGAN PELANGGAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS MELALUI KEPUASAN NASABAH - Sri Rahayu, Basuki (ADVANCE, 2014)
This study aims is to determine the Effects of Service Quality, Customer Relations and Corporate Image Of Loyalty Through Customer Satisfaction In PD. BPR BKK Boyolali. This study is a survey research. The data used primary data collected through questionnaires to customers PD. BPR BKK Boyolali. The data obtained were tested using the test validity, reliability, linearity test, path analysis, t test, F test, test R2 in total. The results of the t test, the first equation shows that the variables of service quality and corporate image/company image respectively positive and significant impact, while customer relationship/effect relationship is positive but not significant. While the second equation only service quality are significant effect on customer loyalty, indicating that due to the location of existing districts in the region, in general, customer-oriented transactions with a sense of security and fast employee service in the transaction of PD. BPR BKK Boyolali. F test results the first equation and the second equation shows that together or simultaneously variable service quality, customer relations/relationships, corporate image/company image, as well as the effect of satisfaction on customer loyalty PD. BPR BKK Boyolali. From the test results obtained by the total R value of 0.755 or 75.50 %. This means that customer loyalty PD. BPR BKK Boyolali. From the total effect shows that the effective path in an effort to increase customer loyalty PD BPR BKK Boyolali is through a variety of efforts to improve service quality variables because in addition to a significant positive effect also has the greatest value or dominant. Boyolali waiter explained by the variable quality, customer relations/relationships, corporate image/company image and customer satisfaction as an intervening variable of 75.50 % and the remaining 24.50 % is explained by other variables outside our model, such as : interest rates, administrative costs banks, promotion, other supporting facilities. The results of path analysis, the use of intervening variables, in this path analysis showed that the variables of satisfaction in order to increase customer loyalty of the variable quality of service, customer relations and corporate image is not effective, because of these three variables showed the direct influence everything bigger than numbers indirect effect. Keywords : Quality of Service , Customer Relations , Corporate Image , job satisfaction, Loyalty.